2018
DOI: 10.1021/acsami.7b16251
|View full text |Cite
|
Sign up to set email alerts
|

Roll-to-Roll Manufacturing of Robust Superhydrophobic Coating on Metallic Engineering Materials

Abstract: Creating a robust superhydrophobic surface on the conventional engineering materials at mass production is of great importance for a self-cleaning, anti-icing, nonwetting surface and low flow resistance in industrial applications. Herein, we report a roll-to-roll strategy to create durable and robust superhydrophobic surfaces with designed micro-/nanoscale hierarchical structures on many conventional engineering materials by combining electrical discharge machining and coating of carbon nanoparticles, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…Instead, the CA can reach or even exceed 150 • by modifying the rough structures with low-surface-energy materials. Therefore, the key to preparing an SHS is the formation of a rough structure and a reduction in surface energy [15]. A large number of approaches were successfully used to develop superhydrophobic surfaces, including chemical etching [16], solution immersion [17], and laser machining [18].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the CA can reach or even exceed 150 • by modifying the rough structures with low-surface-energy materials. Therefore, the key to preparing an SHS is the formation of a rough structure and a reduction in surface energy [15]. A large number of approaches were successfully used to develop superhydrophobic surfaces, including chemical etching [16], solution immersion [17], and laser machining [18].…”
Section: Introductionmentioning
confidence: 99%
“…The Nyquist plots and Bode plots of the titanium surfaces at different processes are shown in Figure 9 b,c. In Nyquist plots, the impedance semicircle diameter is related to polarization resistance, and a larger impedance semicircle diameter represents better corrosion resistance [ 24 , 47 ]. Significantly, the impedance semicircle diameter of the as-prepared superhydrophobic surface increases sharply, approaching ten thousand kΩ·cm 2 ( Figure 9 b), about 16 times compared to the original surface.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical discharge machining (EDM) is a non-contact machining technology as well as an effective method for difficult-to-cut material [ 23 ]. Furthermore, the surface morphology of an EDM machined surface is beneficial for establishing a superhydrophobic surface [ 24 ]. William et al found that the steel surface was a superhydrophobic surface, then machined micro-mushroom re-entrant structures using micro wire EDM [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data shows that, after laser cleaned surface, the anticorrosion potential of is improved when compared with the polished 5A06 aluminum block surface, while the corrosion current density reduced. The previous research shows the thickness of the rust layer has great influence on the corrosion current density [50]. The E corr of the polished 5A06 aluminum block surface was −9.03 × 10 −1 V, in contrast, the E corr of the partially damaged paint layer and the laser treated 5A06 aluminum surface at an intensity of 11.9 W/cm 2 were −8.61 × 10 −1 and −6.39 ×10 −1 V, correspondingly.…”
Section: Samplementioning
confidence: 99%